Local marketing elements and their role in achieving customer satisfaction – A field study on some local banks in the State of Kuwait – - Alshammri, Mohammed Haber (Journal of Economic, Administrative and Legal Sciences, 2021)
The Study aimed to identify the extent of commitment of local banks in the State of Kuwait to work with the concept of marketing internally and externally, and interest in it, and the relationship between training and development of employees in these banks and the extent of customer satisfaction in these banks, and the level of the relationship between employee motivation and the level of customer satisfaction for these banks, and the relationship between delegation of powers to employees And to increase their satisfaction and customer satisfaction.The Study sample consisted of (51) bank references in the State of Kuwait. The study used the questionnaire as a tool for collecting study data. The study applied the descriptive analytical approach. The results of the study reached:The Banks are committed to activating the elements of internal marketing, whether the bank's services or the promotion of services, the efficiency and motivation of workers, and the satisfaction of workers, but the promotion of services came in a lagging position from the point of view of the study sample.The High level of customer satisfaction with banks' services, whether from the good availability of branches for those banks or the speed and simplicity of completing transactions, flexibility in working hours, and following an accurate system in completing transactions.The Elements of internal marketing affect and are significantly related to customer satisfaction and contribute to the level of customer satisfaction.The Bank's services, employee satisfaction, and employee efficiency and motivation are what contribute significantly to customer satisfaction, while promoting services does not affect or contribute to customer satisfaction.There are no statistically significant differences in the averages of each of the marketing elements and customer satisfaction due to the differences in gender, age, educational level and occupation among Kuwaiti bank customers.The study recommended paying attention to the human cadre, relying on electronic methods to provide banking services, and establishing partnerships and alliances between local and foreign banks to benefit from the expertise to develop the elements of banking services.
Keywords: elements of internal marketing; customer satisfaction; human resource performance; local banks; Kuwait